The Effect of Discipline on Learning Independence and Learning Motivation of Fourth Grade Students at MI Miftahul Huda Rawasan Jenu Academic Year 2025/2026 - Nurkholifah Nurkholifah; Ziana Dhurrotul Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research is motivated by the importance of discipline in enhancing student independence and motivation in elementary schools. The purpose of this study was to determine the effect of discipline on learning independence and motivation in fourthgrade students at MI Miftahul Huda Rawasan Jenu in the 2025/2026 academic year. This study used a quantitative approach with a correlational approach. The population in this study was all 30 fourth-grade students at MI Miftahul Huda Rawasan Jenu. Data collection techniques used questionnaires and documentation. Data analysis was conducted through normality tests, linearity tests, multicollinearity tests, Pearson correlation tests, and simple linear regression tests using SPSS. The results showed that discipline had a positive and significant effect on student learning independence, with a significance value of 0.015 < 0.05 and an R-square value of 0.194. Discipline contributed 19.4% to student learning independence. In addition, discipline also has a positive and significant effect on student learning motivation with a significance value of 0.015 < 0.05 and an R Square value of 0.193, so that discipline has a 19.3% effect on student learning motivation. Thus, the higher the level of student discipline, the higher the student's independence and learning motivation.